Short burst oxygen therapy after activities of daily living in the home in chronic obstructive pulmonary disease - Quantrill, S J (BMJ Group, 2007)
BACKGROUND: Short burst oxygen therapy (SBOT) is widely prescribed in the UK with little evidence of benefit. A study was performed to examine whether SBOT benefits patients when undertaking normal activities at home among those who already use it. METHODS: Twenty‐two patients with chronic obstructive pulmonary disease (COPD) were included in the study. All regularly used SBOT at home and claimed that it helps them. Each patient chose two daily living activities for which they used SBOT for relief of breathlessness. Patients were then randomised to use either an air or oxygen gas cylinder. At least 15 min later the same activity was performed using the other gas cylinder. The same process was then repeated for the second chosen activity. The main endpoints were subjective and objective times to recovery, analysed for each activity separately or taking the average over the two activities. A paired statistical analysis was performed. RESULTS: All patients used SBOT with nasal prongs after exercise. Using the average recovery time over two activities for each patient, the mean objective recovery time was 38 s lower (95% CI −81 to +5) using oxygen and the mean subjective recovery time was 34 s lower (95% CI −69 to +2). Five patients were correctly able to distinguish oxygen from air after both activities and there was a suggestion that their recovery times were shorter than those who did not correctly identify the gases (91 s vs 20 s using objective recovery times, and 80 s vs 22 s using subjective recovery times), although this was a subgroup analysis based on only five patients with non‐significant results. CONCLUSIONS: There is some evidence that SBOT shortens recovery time after activities of daily living in a selected group of patients with COPD, but the effect is small. There appears to be a subgroup of patients who may benefit to a much greater degree.